Concrete composite floor for outdoor humid area and preparation method of concrete composite floor
By using concrete laminate floors made of glass fiber, cement and special polyester powder coatings, the problems of mold, cracking and poor flame retardant performance of wood-plastic floors in humid outdoor areas are solved, and high-strength, wear-resistant, non-flammable, Weather-resistant performance, suitable for outdoor wet areas, reducing costs.
Patent Information
- Application Number
- CN202411279619.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
The wood-plastic composite floors in existing outdoor wet areas are prone to mold and cracking during long-term use, have poor flame retardant performance, and are costly, making it difficult to meet the needs of weather resistance and fire safety.
High-strength concrete composite floor made of glass fiber, cement, fine aggregates and special polyester powder coatings, the coating contains homemade polyester resin, curing agent, titanium dioxide, barium sulfate and wetting promoter, through twin screws The extruder melts and extrudes, tablets, cools, crushes, grinds and sieves to make the finished powder coating and is molded by electrostatic spraying and thermal curing.
It realizes high-strength, wear-resistant, non-combustible and weather-resistant concrete composite floors, which are low-cost and are suitable for outdoor wet areas. They replace wood-plastic composite materials and have the advantages of aesthetics, water resistance, weather resistance and high fire safety.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and particularly relates to a concrete composite floor for outdoor wet areas and a preparation method thereof. Background Art
[0002] At present, with the increasing popularity of outdoor decorative materials, the floor of outdoor parks and some areas of outdoor buildings generally used wooden materials in the early days. Due to the lack of outdoor weather resistance, it is easy to rot under long-term wind and sun. At present, wood-plastic composite materials are mainly used. Wood-plastic composite materials are made by mixing wood powder and plastic, such as CN200810021177.4, CN200910099804.0, CN201911351059.4, etc. Compared with wooden floors, they have the advantages of relatively good durability and weather resistance. However, the materials used for outdoor wood-plastic flooring near the river, lake, or mountain wet areas have also had some defects in recent years, such as the existence of easy mold growth, cracking, and poor flame retardant performance in wet areas for a long time, especially the wood-plastic flooring in tourist attractions near the river or lake basically needs to be replaced in about 2 years, and the cost is relatively high. With the improvement of fire safety, how to develop a composite floor that can adapt to long-term outdoor use, good weather resistance, not corroded by mold in wet areas, and excellent self-flammability is particularly important for the application of this field.
[0003] In view of the above problems, the present invention designs a high-strength concrete composite floor for outdoor wet areas, which is made of glass fiber, cement, fine aggregate, water reducer and special polyester powder coating; the polyester powder coating of the concrete composite floor includes self-made polyester resin, curing agent, titanium dioxide, barium sulfate, wetting promoter, leveling agent, etc. First, the required concrete road panel is prepared, and then the prepared polyester powder coating is thickly coated (for example, 140-150μm), and thermally cured to obtain the concrete composite floor of the present invention. This product uses a specially prepared polyester resin product with a special structure and formula and is grafted with quaternary ammonium salt functional groups, which improves adhesion and electrical properties and achieves effective coating with concrete road panel substrates. Compared with ordinary concrete mortar substrates, this composite floor has the advantages of beautiful appearance, high strength, wear resistance, and low water absorption. Compared with the wood-plastic composite flooring currently widely used in outdoor humid areas, it has the advantages of high strength, not easy to deform, water resistance, wear resistance, non-flammability, and excellent weather resistance under the same size, and low cost, so it can be used in outdoor humid areas instead of wood-plastic composite materials. Summary of the invention
[0004] A concrete composite floor for outdoor wet areas, wherein the coating used for the coating of the concrete composite floor comprises the following raw materials in parts by weight:
[0005]
[0006] Furthermore, in the coating used for the coating of the concrete composite floor, the polyester resin is a homemade carboxyl polyester resin; the curing agent is triglycidyl isocyanurate; for example, the model may be PT810, purchased from Huangshan Friendship Nanhai New Materials Co., Ltd.; the wetting promoter, for example, the model is BLC701, purchased from Ningbo Nanhai Chemical Co., Ltd.; the leveling agent, for example, the model is K7572, purchased from Lu'an Jietongda New Materials Co., Ltd.
[0007] The coating used for the above concrete composite floor coating is prepared by: mixing the materials evenly according to the coating formula, then melt-extruding them with a twin-screw extruder, and then tableting, cooling, and crushing them to obtain flakes, and then crushing the flakes by, for example, a mill, and then sieving them to obtain a finished powder coating.
[0008] Preferably, the screw temperature of the twin-screw extruder for melt extrusion is controlled at 130-135° C.; the mesh size of the finished powder coating after sieving is controlled at 160-180.
[0009] In the coating formula of the above concrete composite floor, the self-made polyester resin includes the following raw materials in molar proportions:
[0010]
[0011]
[0012] The catalyst is dibutyltin oxide, and the dosage is 0.3-0.5% of the mass of adipic acid.
[0013] The preparation method of the above polyester resin is:
[0014] (1) Add the formulated amount of N-methyldiethanolamine and anhydrous ethanol into a reaction kettle, start stirring and heat to 70-75° C., then dropwise add the formulated amount of benzyl chloride, and continue to keep the temperature for reaction;
[0015] (2) sampling and testing the amine value of the compound. When the amine value is lower than 3 mgKOH / g, it indicates that the quaternization reaction is basically completed. At this time, the vacuum system is started to remove the solvent ethanol under reduced pressure to obtain the N-methyldiethanolamine product of benzyl chloride quaternization, wherein the reaction temperature is 70-75° C.;
[0016] (3) After no obvious substance is evaporated, the vacuum system is released, and the formulated amount of tetraethylene glycol and the catalyst dibutyltin oxide are added, mixed evenly, and then the temperature is continued to rise to 140-145° C., and then the formulated amount of 12-hydroxystearic acid and adipic acid are added to carry out a preliminary polymerization reaction;
[0017] (4) Sampling and testing the acid value of the polymer. When the acid value of the polymer reaches 130-150 mgKOH / g, the temperature is continuously raised to 210-220° C. and kept at this temperature for polymerization reaction. During the heating process, small molecular water generated during the polymerization process and a small amount of unreacted benzyl chloride are removed;
[0018] (5) sampling and testing the acid value of the polymer. When the acid value of the polymer reaches 60-75 mgKOH / g, adding the formulated amount of 1,6-hexanediol diglycidyl ether, and performing a chain extension polymerization reaction at 220-230° C. When the acid value of the polymer reaches 25-35 mgKOH / g, starting the vacuum system to perform a vacuum polycondensation reaction;
[0019] (6) Sampling and testing the acid value of the polymer. When the acid value reaches 12-20 mgKOH / g, the vacuum system is released, and 4-methoxyphthalic acid is added to carry out carboxyl end-capping reaction. When the acid value of the polymer reaches 33-40 mgKOH / g, the reaction is stopped, the material is discharged at high temperature, and the polyester resin product is obtained by cooling and crushing with a steel belt.
[0020] Preferably, the dropping time of step (1) is controlled at 1-1.5 h; the vacuum degree of step (2) is controlled at -0.092 MPa to -0.095 MPa; the heating rate of step (4) is 15-18°C / h; the vacuum degree of step (5) is controlled at -0.095 MPa to -0.098 MPa; and cooling is performed through a steel belt in step (6).
[0021] The present invention also relates to a concrete composite floor for outdoor wet areas, which is obtained by using the coating of the concrete composite floor for outdoor wet areas described above;
[0022] The base material of the concrete composite floor comprises the following raw materials in parts by weight:
[0023]
[0024]
[0025] Among them, cement is ordinary Portland cement (for example, model PO42.5, purchased from Anhui Conch Cement Co., Ltd.); preferably, fine aggregate is ultra-fine sand with a fineness modulus of 1-1.4; glass fiber is special glass fiber for concrete, with a length of 2-4mm, for example, 3mm standard, purchased from Hebei Jiegui Mineral Products Co., Ltd.; water reducer is polycarboxylic acid high-efficiency water reducer, for example, model XF-3, purchased from Hefei Yongyuan Building Materials Co., Ltd.
[0026] The method for preparing the concrete composite floor for outdoor wet areas as described above comprises the following steps:
[0027] A. Weigh the raw materials of cement, fine aggregate and glass fiber in a completely dry state according to the formula amount, add them into a mixer in sequence, then add the water and water reducing agent according to the formula amount, and stir the mixture evenly according to the stirring method of low-speed stirring (for example, 90s) + high-speed stirring (for example, 50s) + stop stirring (for example, 120s) + high-speed stirring (for example, 90s); load the stirred mixture into the experimental mold in layers, and place the experimental mold on a vibration table and vibrate it for example, 120 times; the vibration-formed test block is cured with the mold, for example, for 24 hours, and then the mold is removed, and the test block is moved into a standard curing room (20±2℃, relative humidity is 75%), and after curing (for example, up to 28 days), it is taken out and fully dried for use;
[0028] B. Hang the concrete substrate obtained in step A on an electrostatic spraying line, and then electrostatically spray the polyester powder coating prepared above, for example, with a film thickness of 140-150 μm, and cure (for example, at 185° C. / 15 min) to obtain a high-strength concrete composite floor.
[0029] Beneficial effects:
[0030] The present invention relates to a high-strength concrete composite floor for outdoor wet areas, which is made of glass fiber, cement, fine aggregate, water reducing agent and special polyester powder coating; the polyester powder coating (coating) of the concrete composite floor includes self-made polyester resin, curing agent, titanium dioxide, barium sulfate, wetting promoter, leveling agent, etc. Firstly, the required concrete road panel is prepared, and then the prepared polyester powder coating is thickly coated and thermoset to obtain the concrete composite floor of the present invention.
[0031] Regarding the polyester resin with a special molecular structure described in the present invention, the quaternary ammonium salt structure first obtained by N-methyldiethanolamine and benzyl chloride gives the polyester resin a charge, and the amino group of N-methyldiethanolamine and the glycerol ether group of 1,6-hexanediol diglycidyl ether increase the adhesion of the polyester resin to the substrate, and at the same time, through the combination of N-methyldiethanolamine, adipic acid, triethylene glycol, 12-hydroxystearic acid and 1,6-hexanediol diglycidyl ether, a polyester resin with excellent flexibility is obtained, and the end-capping of 4-methoxyphthalic acid improves the water resistance of the polyester resin.
[0032] It can be seen that in the concrete composite floor for outdoor wet areas of the present invention, a specific polyester resin product is used, a special structure and formula are adopted, and a quaternary ammonium salt functional group is grafted, so that the adhesion and charging performance are improved, and effective coating with the concrete road panel substrate is achieved. Compared with the ordinary concrete mortar substrate, the composite floor has the advantages of beautiful appearance, high strength, wear resistance, low water absorption, etc. Compared with the wood-plastic composite floor widely used in outdoor wet areas, it has the advantages of high strength under the same size, not easy to deform, and excellent water resistance, wear resistance, and weather resistance.
[0033] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. DETAILED DESCRIPTION
[0034] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.
[0035] Among them, in the coating corresponding to the coating of the concrete composite floor, the polyester resin is a homemade carboxyl polyester resin (the method is described in the embodiment); the curing agent is triglycidyl isocyanurate; the model is PT810, purchased from Huangshan Friendship Nanhai New Materials Co., Ltd.; the wetting promoter model is BLC701, purchased from Ningbo Nanhai Chemical Co., Ltd.; the leveling agent model is K7572, purchased from Lu'an Jietongda New Materials Co., Ltd.
[0036] Among them, in the base material of the concrete composite floor, the cement is ordinary Portland cement, model PO42.5, purchased from Anhui Conch Cement Co., Ltd.; the fine aggregate is ultra-fine sand with a fineness modulus of 1-1.4; the glass fiber is special glass fiber for concrete, with a standard length of 3mm, purchased from Hebei Jiegui Mineral Products Co., Ltd.; the water reducer is a polycarboxylic acid high-efficiency water reducer, model XF-3, purchased from Hefei Yongyuan Building Materials Co., Ltd.
[0037] Except for the above description, other raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.
[0038] Example 1
[0039] A concrete composite floor for outdoor wet areas, wherein the coating of the concrete composite floor corresponds to a coating comprising the following raw materials in parts by weight:
[0040]
[0041] The preparation method of the coating for the concrete composite floor is as follows: the materials are mixed evenly according to the coating formula, and then melt-extruded by a twin-screw extruder, and then the flakes are obtained by tableting, cooling, and crushing, and then the flakes are crushed by a mill and sieved to obtain a finished powder coating. The screw temperature of the twin-screw extruder for melt extrusion is controlled at 130-135°C; the mesh size of the finished powder coating is controlled at 160-180 after sieving.
[0042] In the coating formula of the above concrete composite floor, the self-made polyester resin includes the following raw materials in molar proportions:
[0043]
[0044] The catalyst is dibutyltin oxide, and the amount used is 0.4% of the mass of adipic acid.
[0045] The preparation method of the above polyester resin is:
[0046] (1) Add the formulated amount of N-methyldiethanolamine and anhydrous ethanol into a reaction kettle, start stirring and heat to 70-75° C., then dropwise add the formulated amount of benzyl chloride, the dropping time is controlled to be 1-1.5 hours, and then continue to keep warm for reaction;
[0047] (2) Sampling and testing the amine value of the compound. When the amine value is lower than 3 mgKOH / g, it indicates that the quaternization reaction is basically completed. At this time, the vacuum system is started to remove the solvent ethanol under reduced pressure to obtain the N-methyldiethanolamine product of benzyl chloride quaternization, wherein the vacuum degree is controlled at -0.092 MPa to -0.095 MPa and the reaction temperature is 70-75°C;
[0048] (3) After no obvious substance is evaporated, the vacuum system is released, and the formulated amount of tetraethylene glycol and the catalyst dibutyltin oxide are added, mixed evenly, and then the temperature is continued to rise to 140-145° C., and then the formulated amount of 12-hydroxystearic acid and adipic acid are added to carry out a preliminary polymerization reaction;
[0049] (4) Sampling and testing the acid value of the polymer. When the acid value of the polymer reaches 130-150 mgKOH / g, the temperature is continuously raised to 210-220° C. and kept at this temperature for polymerization reaction. The heating rate is 15-18° C. / h. During the heating process, small molecular water generated during the polymerization process and a small amount of unreacted benzyl chloride are removed;
[0050] (5) sampling and testing the acid value of the polymer. When the acid value of the polymer reaches 60-75 mgKOH / g, adding the formulated amount of 1,6-hexanediol diglycidyl ether, and performing a chain extension polymerization reaction at 220-230° C. When the acid value of the polymer reaches 25-35 mgKOH / g, starting the vacuum system to perform a vacuum polycondensation reaction, and the vacuum degree is controlled at -0.095 MPa to -0.098 MPa;
[0051] (6) Sampling and testing the acid value of the polymer. When the acid value reaches 12-20 mgKOH / g, the vacuum system is released, and 4-methoxyphthalic acid is added to carry out carboxyl end-capping reaction. When the acid value of the polymer reaches 33-40 mgKOH / g, the reaction is stopped, the material is discharged at high temperature, and the polyester resin product is obtained by cooling and crushing with a steel belt.
[0052] A concrete composite floor for outdoor wet areas, obtained by using the coating of the concrete composite floor for outdoor wet areas;
[0053] The base material of the concrete composite floor comprises the following raw materials in parts by weight:
[0054]
[0055] The method for preparing the concrete composite floor for outdoor wet areas as described above comprises the following steps:
[0056] A. Weigh the raw materials of cement, fine aggregate and glass fiber in a completely dry state in the formula amount, add them into the mixer in sequence, then add the water and water reducing agent in the formula amount, and stir the mixture evenly by stirring at low speed (90s) + high speed stirring (50s) + stop stirring (120s) + high speed stirring (90s); load the stirred mixture into the experimental mold in layers, and place the experimental mold on the vibration table to vibrate 120 times; after curing the vibration-formed test block with the mold for 24 hours, remove the mold, move the test block into a standard curing room (20±2℃, relative humidity of 75%), take it out after curing for 28 days, and set it aside after it is fully dried;
[0057] B. Hang the concrete substrate obtained in step A on an electrostatic spraying line, and then electrostatically spray the polyester powder coating prepared above to a film thickness of 150 μm, and cure at 185° C. / 15 min to obtain a high-strength concrete composite floor.
[0058] Example 2
[0059] A concrete composite floor for outdoor wet areas, wherein the coating used for the coating of the concrete composite floor comprises the following raw materials in parts by weight:
[0060]
[0061] The preparation method of the coating for the concrete composite floor is as follows: the materials are mixed evenly according to the coating formula, and then melt-extruded by a twin-screw extruder, and then the flakes are obtained by tableting, cooling, and crushing, and then the flakes are crushed by a mill and sieved to obtain a finished powder coating. The screw temperature of the twin-screw extruder for melt extrusion is controlled at 130-135°C; the mesh size of the finished powder coating is controlled at 160-180 after sieving.
[0062] In the coating formula of the above concrete composite floor, the self-made polyester resin includes the following raw materials in molar proportions:
[0063]
[0064] The catalyst is dibutyltin oxide, and the amount used is 0.5% of the mass of adipic acid.
[0065] The preparation method of the above polyester resin is:
[0066] (1) Add the formulated amount of N-methyldiethanolamine and anhydrous ethanol into a reaction kettle, start stirring and heat to 70-75° C., then dropwise add the formulated amount of benzyl chloride, the dropping time is controlled to be 1-1.5 hours, and then continue to keep warm for reaction;
[0067] (2) Sampling and testing the amine value of the compound. When the amine value is lower than 3 mgKOH / g, it indicates that the quaternization reaction is basically completed. At this time, the vacuum system is started to remove the solvent ethanol under reduced pressure to obtain the N-methyldiethanolamine product of benzyl chloride quaternization, wherein the vacuum degree is controlled at -0.092 MPa to -0.095 MPa and the reaction temperature is 70-75°C;
[0068] (3) After no obvious substance is evaporated, the vacuum system is released, and the formulated amount of tetraethylene glycol and the catalyst dibutyltin oxide are added, mixed evenly, and then the temperature is continued to rise to 140-145° C., and then the formulated amount of 12-hydroxystearic acid and adipic acid are added to carry out a preliminary polymerization reaction;
[0069] (4) Sampling and testing the acid value of the polymer. When the acid value of the polymer reaches 130-150 mgKOH / g, the temperature is continuously raised to 210-220° C. and kept at this temperature for polymerization reaction. The heating rate is 15-18° C. / h. During the heating process, small molecular water generated during the polymerization process and a small amount of unreacted benzyl chloride are removed;
[0070] (5) sampling and testing the acid value of the polymer. When the acid value of the polymer reaches 60-75 mgKOH / g, adding the formulated amount of 1,6-hexanediol diglycidyl ether, and performing a chain extension polymerization reaction at 220-230° C. When the acid value of the polymer reaches 25-35 mgKOH / g, starting the vacuum system to perform a vacuum polycondensation reaction, and the vacuum degree is controlled at -0.095 MPa to -0.098 MPa;
[0071] (6) Sampling and testing the acid value of the polymer. When the acid value reaches 12-20 mgKOH / g, the vacuum system is released, and 4-methoxyphthalic acid is added to carry out carboxyl end-capping reaction. When the acid value of the polymer reaches 33-40 mgKOH / g, the reaction is stopped, the material is discharged at high temperature, and the polyester resin product is obtained by cooling and crushing with a steel belt.
[0072] A concrete composite floor for outdoor wet areas, obtained by using the coating of the concrete composite floor for outdoor wet areas;
[0073] The base material of the concrete composite floor comprises the following raw materials in parts by weight:
[0074]
[0075]
[0076] The method for preparing the concrete composite floor for outdoor wet areas as described above comprises the following steps:
[0077] A. Weigh the raw materials of cement, fine aggregate and glass fiber in a completely dry state in the formula amount, add them into the mixer in sequence, then add the water and water reducing agent in the formula amount, and stir the mixture evenly by stirring at low speed (90s) + high speed stirring (50s) + stop stirring (120s) + high speed stirring (90s); load the stirred mixture into the experimental mold in layers, and place the experimental mold on the vibration table to vibrate 120 times; after curing the vibration-formed test block with the mold for 24 hours, remove the mold, move the test block into a standard curing room (20±2℃, relative humidity of 75%), take it out after curing for 28 days, and set it aside after it is fully dried;
[0078] B. Hang the concrete substrate obtained in step A on an electrostatic spraying line, and then electrostatically spray the polyester powder coating prepared above to a film thickness of 150 μm, and cure at 185° C. / 15 min to obtain a high-strength concrete composite floor.
[0079] Example 3
[0080] A concrete composite floor for outdoor wet areas, wherein the coating used for the coating of the concrete composite floor comprises the following raw materials in parts by weight:
[0081]
[0082] The preparation method of the coating for the concrete composite floor is as follows: the materials are mixed evenly according to the coating formula, and then melt-extruded by a twin-screw extruder, and then the flakes are obtained by tableting, cooling, and crushing, and then the flakes are crushed by a mill and sieved to obtain a finished powder coating. The screw temperature of the twin-screw extruder for melt extrusion is controlled at 130-135°C; the mesh size of the finished powder coating is controlled at 160-180 after sieving.
[0083] In the coating formula of the above concrete composite floor, the self-made polyester resin includes the following raw materials in molar proportions:
[0084]
[0085]
[0086] The catalyst is dibutyltin oxide, and the amount used is 0.45% of the mass of adipic acid.
[0087] The preparation method of the above polyester resin is:
[0088] (1) Add the formulated amount of N-methyldiethanolamine and anhydrous ethanol into a reaction kettle, start stirring and heat to 70-75° C., then dropwise add the formulated amount of benzyl chloride, the dropping time is controlled to be 1-1.5 hours, and then continue to keep warm for reaction;
[0089] (2) Sampling and testing the amine value of the compound. When the amine value is lower than 3 mgKOH / g, it indicates that the quaternization reaction is basically completed. At this time, the vacuum system is started to remove the solvent ethanol under reduced pressure to obtain the N-methyldiethanolamine product of benzyl chloride quaternization, wherein the vacuum degree is controlled at -0.092 MPa to -0.095 MPa and the reaction temperature is 70-75°C;
[0090] (3) After no obvious substance is evaporated, the vacuum system is released, and the formulated amount of tetraethylene glycol and the catalyst dibutyltin oxide are added, mixed evenly, and then the temperature is continued to rise to 140-145° C., and then the formulated amount of 12-hydroxystearic acid and adipic acid are added to carry out a preliminary polymerization reaction;
[0091] (4) Sampling and testing the acid value of the polymer. When the acid value of the polymer reaches 130-150 mgKOH / g, the temperature is continuously raised to 210-220° C. and kept at this temperature for polymerization reaction. The heating rate is 15-18° C. / h. During the heating process, small molecular water generated during the polymerization process and a small amount of unreacted benzyl chloride are removed;
[0092] (5) sampling and testing the acid value of the polymer. When the acid value of the polymer reaches 60-75 mgKOH / g, adding the formulated amount of 1,6-hexanediol diglycidyl ether, and performing a chain extension polymerization reaction at 220-230° C. When the acid value of the polymer reaches 25-35 mgKOH / g, starting the vacuum system to perform a vacuum polycondensation reaction, and the vacuum degree is controlled at -0.095 MPa to -0.098 MPa;
[0093] (6) Sampling and testing the acid value of the polymer. When the acid value reaches 12-20 mgKOH / g, the vacuum system is released, and 4-methoxyphthalic acid is added to carry out carboxyl end-capping reaction. When the acid value of the polymer reaches 33-40 mgKOH / g, the reaction is stopped, the material is discharged at high temperature, and the polyester resin product is obtained by cooling and crushing with a steel belt.
[0094] Concrete composite floor for outdoor wet areas, obtained by using the coating material for the concrete composite floor for outdoor wet areas;
[0095] The base material of the concrete composite floor comprises the following raw materials in parts by weight:
[0096]
[0097] The method for preparing the concrete composite floor for outdoor wet areas as described above comprises the following steps:
[0098] A. Weigh the raw materials of cement, fine aggregate and glass fiber in a completely dry state in the formula amount, add them into the mixer in sequence, then add the water and water reducing agent in the formula amount, and stir the mixture evenly by stirring at low speed (90s) + high speed stirring (50s) + stop stirring (120s) + high speed stirring (90s); load the stirred mixture into the experimental mold in layers, and place the experimental mold on the vibration table to vibrate 120 times; after curing the vibration-formed test block with the mold for 24 hours, remove the mold, move the test block into a standard curing room (20±2℃, relative humidity of 75%), take it out after curing for 28 days, and set it aside after it is fully dried;
[0099] B. Hang the concrete substrate obtained in step A on an electrostatic spraying line, and then electrostatically spray the polyester powder coating prepared above to a film thickness of 150 μm, and cure at 185° C. / 15 min to obtain a high-strength concrete composite floor.
[0100] Example 4
[0101] A concrete composite floor for outdoor wet areas, wherein the coating of the concrete composite floor corresponds to a coating comprising the following raw materials in parts by weight:
[0102]
[0103]
[0104] The preparation method of the coating corresponding to the coating of the above concrete composite floor is as follows: the materials are mixed evenly according to the coating formula, and then melt-extruded by a twin-screw extruder, and then the flakes are obtained by tableting, cooling, and crushing, and then the flakes are crushed by a mill and sieved to obtain the finished powder coating. The screw temperature of the twin-screw extruder for melt extrusion is controlled at 130-135°C; the mesh size of the sieved finished powder coating is controlled at 160-180.
[0105] In the coating formula of the above concrete composite floor, the self-made polyester resin includes the following raw materials in molar proportions:
[0106]
[0107] The catalyst is dibutyltin oxide, and the amount used is 0.5% of the mass of adipic acid.
[0108] The preparation method of the above polyester resin is:
[0109] (1) Add the formulated amount of N-methyldiethanolamine and anhydrous ethanol into a reaction kettle, start stirring and heat to 70-75° C., then dropwise add the formulated amount of benzyl chloride, the dropping time is controlled to be 1-1.5 hours, and then continue to keep warm for reaction;
[0110] (2) Sampling and testing the amine value of the compound. When the amine value is lower than 3 mgKOH / g, it indicates that the quaternization reaction is basically completed. At this time, the vacuum system is started to remove the solvent ethanol under reduced pressure to obtain the N-methyldiethanolamine product of benzyl chloride quaternization, wherein the vacuum degree is controlled at -0.092 MPa to -0.095 MPa and the reaction temperature is 70-75°C;
[0111] (3) After no obvious substance is evaporated, the vacuum system is released, and the formulated amount of tetraethylene glycol and the catalyst dibutyltin oxide are added, mixed evenly, and then the temperature is continued to rise to 140-145° C., and then the formulated amount of 12-hydroxystearic acid and adipic acid are added to carry out a preliminary polymerization reaction;
[0112] (4) Sampling and testing the acid value of the polymer. When the acid value of the polymer reaches 130-150 mgKOH / g, the temperature is continuously raised to 210-220° C. and kept at this temperature for polymerization reaction. The heating rate is 15-18° C. / h. During the heating process, small molecular water generated during the polymerization process and a small amount of unreacted benzyl chloride are removed;
[0113] (5) sampling and testing the acid value of the polymer. When the acid value of the polymer reaches 60-75 mgKOH / g, adding the formulated amount of 1,6-hexanediol diglycidyl ether, and performing a chain extension polymerization reaction at 220-230° C. When the acid value of the polymer reaches 25-35 mgKOH / g, starting the vacuum system to perform a vacuum polycondensation reaction, and the vacuum degree is controlled at -0.095 MPa to -0.098 MPa;
[0114] (6) Sampling and testing the acid value of the polymer. When the acid value reaches 12-20 mgKOH / g, the vacuum system is released, and 4-methoxyphthalic acid is added to carry out carboxyl end-capping reaction. When the acid value of the polymer reaches 33-40 mgKOH / g, the reaction is stopped, the material is discharged at high temperature, and the polyester resin product is obtained by cooling and crushing with a steel belt.
[0115] The present invention also relates to a concrete composite floor for outdoor wet areas, which is obtained by using the coating of the concrete composite floor for outdoor wet areas described above;
[0116] The base material of the concrete composite floor comprises the following raw materials in parts by weight:
[0117]
[0118] The method for preparing the concrete composite floor for outdoor wet areas as described above comprises the following steps:
[0119] A. Weigh the raw materials of cement, fine aggregate and glass fiber in a completely dry state in the formula amount, add them into the mixer in sequence, then add the water and water reducing agent in the formula amount, and stir the mixture evenly by stirring at low speed (90s) + high speed stirring (50s) + stop stirring (120s) + high speed stirring (90s); load the stirred mixture into the experimental mold in layers, and place the experimental mold on the vibration table to vibrate 120 times; after curing the vibration-formed test block with the mold for 24 hours, remove the mold, move the test block into a standard curing room (20±2℃, relative humidity of 75%), take it out after curing for 28 days, and set it aside after it is fully dried;
[0120] B. Hang the concrete substrate obtained in step A on an electrostatic spraying line, and then electrostatically spray the polyester powder coating prepared above to a film thickness of 150 μm, and cure at 185° C. / 15 min to obtain a high-strength concrete composite floor.
[0121] Comparative Example 1:
[0122] The wood-plastic composite material of Example 1 in ZL200810021177.4 was used as Comparative Example 1.
[0123] Test method:
[0124] The static bending strength (three-point bending), boiling water resistance, paint film adhesion and accelerated aging performance tests are carried out according to GB / T17657-2013 "Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels"; the flame retardant performance of the sample is tested by the oxygen index GB / T2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test".
[0125] The test results of the concrete composite floors prepared in the above examples and comparative examples are shown in Table 1 below.
[0126] Table 1 Performance test of concrete composite floor
[0127]
[0128]
[0129] As can be seen from Table 1, the surface of the high-strength concrete composite floor prepared by the product of the present invention is flat and smooth, and the appearance is good. In addition, the concrete composite floor itself is non-flammable, and there is still no sign of flammability when the oxygen index reaches 40%, indicating that the fire safety level is extremely high. At the same time, the static bending strength reaches more than 50Mpa, which is much higher than that of ordinary wood-plastic composite materials. The adhesion of the coating is good, reaching level 1 or above, and there is no change on the surface after boiling in boiling water for 2 hours. In particular, in terms of aging resistance, after 15 cycles of accelerated aging tests, no cracks are generated on the surface of the sample, and the outdoor aging resistance is good, which is suitable for application in outdoor fields.
[0130] Comparative Example 1 is a conventional wood-plastic composite floor prepared by Example 1 of ZL200810021177.4, whose surface is basically flat, and its oxygen index is lower than 28% in terms of flame retardancy, which belongs to a combustible material, has a low fire safety level, and its static bending strength is also much lower than that of the product of the present invention. After boiling in boiling water for 2 hours, the surface has a slight gloss loss phenomenon. After 15 cycles of accelerated aging test, multiple cracks appear on the surface of the wood-plastic composite material, affecting its long-term durability outdoors.
[0131] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.
Claims
1. A concrete composite floor for outdoor wet areas, characterized in that: The coating used for the coating of the concrete composite floor comprises the following raw materials in parts by weight:
2. A concrete composite floor for outdoor wet areas as claimed in claim 1, further characterized in that, in the coating used for the coating of the concrete composite floor, the polyester resin is a carboxyl polyester resin; and the curing agent is triglycidyl isocyanurate.
3. A concrete composite floor for outdoor wet areas as claimed in claim 1 or 2, characterized in that: The preparation method of the coating used for the coating of the concrete composite floor is as follows: various materials are mixed evenly according to the coating formula, and then melt-extruded by a twin-screw extruder, and then the flakes are obtained by tableting, cooling, and crushing, and then the flakes are crushed and sieved to obtain powder coating.
4. A concrete composite floor for outdoor wet areas as claimed in claim 3, characterized in that: In the method for preparing the coating used for the coating of the concrete composite floor, the screw temperature of the twin-screw extruder for melt extrusion is 130-135° C.; the finished powder coating obtained by sieving is controlled to have a mesh size of 160-180.
5. A concrete composite floor for outdoor wet areas as claimed in claim 1 or 2, characterized in that: In the coating formula used for the coating of the concrete composite floor, the polyester resin includes the following raw materials in molar proportions: The catalyst is dibutyltin oxide, and the dosage is 0.3-0.5% of the mass of adipic acid.
6. A concrete composite floor for outdoor wet areas as claimed in claim 5, characterized in that: In the coating formulation used for the coating of the concrete composite floor, the preparation method of the polyester resin used is as follows: (1) Add the formulated amount of N-methyldiethanolamine and anhydrous ethanol into a reaction kettle, start stirring and heat to 70-75° C., then dropwise add the formulated amount of benzyl chloride, and continue to keep the temperature for reaction; (2) sampling and testing the amine value of the compound. When the amine value is lower than 3 mgKOH / g, the vacuum system is started to remove the solvent ethanol under reduced pressure to obtain the N-methyldiethanolamine product of benzyl chloride quaternary ammonium salt. The reaction temperature is 70-75° C.; (3) After no obvious substance is evaporated, the vacuum system is released, and the formulated amount of tetraethylene glycol and the catalyst dibutyltin oxide are added, mixed evenly, and then the temperature is continued to rise to 140-145° C., and then the formulated amount of 12-hydroxystearic acid and adipic acid are added to carry out a preliminary polymerization reaction; (4) Sampling and testing the acid value of the polymer. When the acid value of the polymer reaches 130-150 mgKOH / g, the temperature is continuously raised to 210-220° C. and kept at this temperature for polymerization reaction. During the heating process, small molecular water generated during the polymerization process and a small amount of unreacted benzyl chloride are removed; (5) sampling and testing the acid value of the polymer. When the acid value of the polymer reaches 60-75 mgKOH / g, adding the formulated amount of 1,6-hexanediol diglycidyl ether, and performing a chain extension polymerization reaction at 220-230° C. When the acid value of the polymer reaches 25-35 mgKOH / g, starting the vacuum system to perform a vacuum polycondensation reaction; (6) Sampling and testing the acid value of the polymer. When the acid value reaches 12-20 mgKOH / g, the vacuum system is released, and 4-methoxyphthalic acid is added to carry out carboxyl end-capping reaction. When the acid value of the polymer reaches 33-40 mgKOH / g, the reaction is stopped, the material is discharged at high temperature, and the polyester resin product is obtained after cooling and crushing.
7. A concrete composite floor for outdoor wet areas as claimed in claim 6, further characterized in that, in the preparation method of the polyester resin used, the dripping time of step (1) is controlled at 1-1.5 hours; the vacuum degree of step (2) is controlled at -0.092 MPa to -0.095 MPa; the heating rate of step (4) is 15-18°C / h; the vacuum degree of step (5) is controlled at -0.095 MPa to -0.098 MPa; and the step (6) is cooled by a steel belt.
8. A concrete composite floor for outdoor wet areas, obtained by using the coating for a concrete composite floor for outdoor wet areas according to any one of claims 1 to 7; in, The base material of the concrete composite floor comprises the following raw materials in parts by weight:
9. A concrete composite floor for outdoor wet areas as claimed in claim 8, further characterized in that the fine aggregate is ultra-fine sand with a fineness modulus of 1-1.4; the glass fiber is special glass fiber for concrete with a length of 2-4 mm; and the water reducer is a polycarboxylic acid water reducer.
10. A method for preparing a concrete composite floor for outdoor wet areas according to claim 8 or 9, characterized in that: The following steps are involved: A. Weigh the raw materials of cement, fine aggregate and glass fiber in a completely dry state according to the formula, add them into the mixer in sequence, then add the water and water reducing agent according to the formula, and stir the mixture evenly by stirring at low speed + high speed + stop stirring + high speed; load the stirred mixture into the experimental mold in layers, and place the experimental mold on the vibration table for vibration; after curing the vibration-formed test block with the mold, remove the mold, move the test block into the standard curing room, take it out after curing, and set it aside after being fully dried; B. Hang the concrete substrate obtained in step A on an electrostatic spraying line, and then electrostatically spray the coating obtained in any one of claims 1 to 7, with the film thickness controlled at 140-150 μm, and solidify to obtain a concrete composite floor.
Citation Information
Patent Citations
Fiber cement flooring products and methods for the production thereof
CN110325486A
Low-temperature curing high-leveling polyester resin as well as preparation method and application thereof
CN116948157A
Freeze-thaw-resistant and high-fracture-resistant concrete mortar panel and preparation method thereof
CN117844351A
